An overview of Alpine and Mediterranean palaeogeography, terrestrial ecosystems and climate history during MIS 3 with focus on the Middle to Upper Palaeolithic transition. (20th June 2020) - Badino, Federica; Pini, Roberta; Ravazzi, Cesare; Margaritora, Davide; Arrighi, Simona; Bortolini, Eugenio; Figus, Carla; Giaccio, Biagio; Lugli, Federico; Marciani, Giulia; Monegato, Giovanni; Moroni, Adriana; et al.
Abstract: This paper summarizes the current state of knowledge about the millennial scale climate variability characterizing Marine Isotope Stage 3 (MIS 3) in S-Europe and the Mediterranean area and its effects on terrestrial ecosystems. The sequence of Dansgaard-Oeschger events, as recorded by Greenland ice cores and recognizable in isotope profiles from speleothems and high-resolution palaeoecological records, led to dramatic variations in glacier extent and sea level configuration with major impacts on the physiography and vegetation patterns, both latitudinally and altitudinally. The recurrent succession of (open) woodlands, including temperate taxa, and grasslands with xerophytic elements, have been tentatively correlated to GIs in Greenland ice cores. Concerning colder phases, the Greenland Stadials (GSs) related to Heinrich events (HEs) appear to have a more pronounced effect than other GSs on woodland withdrawal and xerophytes expansion. Notably, GS 9-HE4 phase corresponds to the most severe reduction of tree cover in a number of Mediterranean records. On a long-term scale, a reduction/opening of forests throughout MIS 3 started from Greenland Interstadials (GIs) 14/13 (ca. 55–48 ka), which show a maximum in woodland density. At that time, natural environments were favourable for Anatomically Modern Humans (AMHs) to migrate from Africa into Europe as documented by industries associated with modern hominin remains in the Levant. Afterwards, a variety of early Upper Palaeolithic cultures emerged (e.g., Uluzzian and Proto-Aurignacian). In this chronostratigraphic framework, attention is paid to the Campanian Ignimbrite tephra marker, as a pivotal tool for deciphering and correlating several temporal-spatial issues crucial for understanding the interaction between AMHs and Neandertals at the time of the Middle to Upper Palaeolithic transition.